EFFECT OF SOIL TYPE AND MYCORRHIZA INOCULATES ON GROWTH, YIELD AND CHEMICAL COMPONENTS OF SALVIA OFFICINALIS L. - S. Selim; F. Matter; Mahassen Sidky; M. Sabra (Scientific Journal of Flowers and Ornamental Plants)
The present study was conducted on sage (Salvia officinalis L.) plants throughout two successive seasons 2020/2021 and 2021/2022 at a private farm in Fayoum Governorate, Egypt. The experiments aimed to find out the individual and the combined effects of mycorrhiza inoculates at three concentrations (2, 4 and 8 g/plant) under two types of soils (clay and sandy) on vegetative growth, chemical composition and essential oil components of Salvia officinalis. The results emphasized that using mycorrhiza inoculate under two types of soils significantly affected all vegetative growth parameters in this study. Likewise, increased oil percentage and chemical constituents of sage essential oil were obtained especially using clay soil and high levels of mycorrhiza. Additionally, the interaction between soil type and levels of mycorrhiza improved all the studied parameters, particularly by using the combinations between mycorrhiza at 8 g/plant under clay soil.